The Effect of Accounting Digitalization on the Financial Performance of MSMEs Post-COVID-19 Pandemic - Trudy Maryona Nussy; Jacomina Vonny Litamahuputty (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The COVID-19 pandemic has underscored the need for digital transformation, particularly among Micro, Small, and Medium Enterprises (MSMEs), which often lack financial resilience during crises. This study investigates the impact of accounting digitalization on the financial performance of MSMEs in the post pandemic recovery period. It aims to explore how digital accounting tools influence profitability, liquidity, and operational efficiency, and to examine the moderating role of digital maturity in this relationship. A qualitative case study method was employed, utilizing semi structured interviews and document analysis from selected MSMEs that had adopted digital accounting systems for at least one year. Thematic analysis revealed that digitalization led to measurable improvements in financial indicators, including increased net profit margins, better current ratios, and reduced operational costs. Moreover, enterprises with higher digital maturity experienced significantly stronger financial gains, highlighting the role of internal readiness in maximizing the benefits of digital tools. However, common challenges such as poor internet connectivity, limited technical skills, and resistance to change were also identified as barriers to successful implementation. The study concludes that accounting digitalization can serve as a strategic recovery mechanism for MSMEs, provided that adequate digital infrastructure and training support are in place. These findings contribute to the literature by empirically linking digital practices with financial outcomes in a post crisis setting and offer practical insights for policymakers and practitioners aiming to promote digital adoption among MSMEs.